The BUSINESS PLAN KECAP SEHAT BERBAHAN UBI UNGU SEBAGAI BENTUK KEARIFAN LOKAL - Annida, Zulfa; Nangimah, Fajri Ngainatun; Vidella, Raina; Maulidiya, Salwa; Yovania, Indah (JURNAL MAHASISWA BINA INSANI; Vol 10 No 3 (2025): Jurnal Mahasiswa Bina Insani (November 2025)DO - 10.51211/jmbi.v10i3.3847, 2026)
Abstrac: This research aims to develop and analyze the business feasibility of innovative soy sauce products made from soybeans and purple sweet potatoes named si ungu soy sauce. The background of this research is based on the increasing need for food products that are healthy, natural, and have added value from local ingredients. Purple sweet potato is known to contain anthocyanin compounds that act as natural antioxidants and provide natural color to products. The approaches used include product analysis, market analysis, operational aspects, human resources, as well as financial analysis and business strategy. The results of the study show that si ungu soy sauce has advantages in terms of using natural ingredients without preservatives, better nutritional content, and taste that remains in accordance with people's tastes. From the market side, this product has considerable opportunities with target family consumers and the younger generation who care about health. Financial analysis shows that this business is feasible to run with a positive profit value, relatively fast return on capital, and sustainable growth potential. Thus, the si ungu soy sauce business can be an alternative to innovative soy sauce products that are competitive and support the use of local foodstuffs.   Keywords : innovative soy sauce; purple sweet potato; business feasibility; functional food; anthocyanin